STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI POJECT LEADER, ACCOUNT EXECUTIVE DAN PROGRAM MANAGER - Syach Jehan Hussein Faizal; Agus Naryoso (Interaksi Online, 2026)
The development of social media has reshaped digital communication patterns, particularly inhow educational institutions disseminate information. Diponegoro University utilizes the@undip.official account as a platform for public communication, information sharing, andinstitutional branding. However, content management still needs optimization to improveaudience engagement. This professional project aims to implement a digital communicationstrategy through video content production on TikTok and Instagram (@undip.official) to increaseengagement. The process was conducted through pre-production, production, and postproductionstages,usingtheAISASmodel(Attention,Interest,Search,Action,Share).Theauthorservedas Project Leader, Account Executive, and Program Manager, overseeing projectexecution, aligning strategies with institutional goals, and coordinating program implementation.The results show an increase in content production from 45 to 75 pieces, accompanied by higheraudience interactions such as likes, comments, and shares. Thus, optimizing creative content strategies can enhance the effectiveness of social media for institutional communication.